THE STUDY OF ABU HANIFA’S PERSONALITY AND SCHOLARLY LEGACY (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the life and scholarly legacy of Abu Hanifa alNuʿman ibn Thabit within the integrated framework of jurisprudence (fiqh) and theology(ʿaqida). The study analyzes Abu Hanifa’s fiqh methodology alongside his theologicalviews, his contribution to the science of kalam, his positions on matters of creed andfaith, and the influence his theological school subsequently exercised on the formationof the Maturidi tradition. The article further examines in detail the principal worksattributed to Abu Hanifa – “al-Fiqh al-Akbar,” “al-Fiqh al-Absat,” “al-ʿAlim wa-lMutaʿallim,” “al-Risala,” and “al-Wasiyya” – their chains of transmission (isnad), thescholarly debates surrounding their authenticity, and the history of their manuscriptsand printed editions.
Keywords: Abu Hanifa; fiqh; ʿaqida; kalam; Maturidism; Hanafi madhhab; al-Fiqh al-Akbar; Companion; Follower (tabiʿun); Sunni theology; isnad.